New species of caddisflies (Insecta: Trichoptera) from emergence traps at streams in central Palawan, Philippines - Freitag, Hendrik (Archīum Ateneo, 2019)
New species of Trichoptera were identified in samples collected from emergence traps along two streams (Cabayugan River and Panaguman River) at Puerto Princesa Subterranean River National Park, Palawan, Philippines in 2000–2001. The species are described as: Orthotrichia ligula sp. n., Chrysotrichia minutula sp. n., Chimarra ligula sp. n., Pahamunaya panagumani sp. n., Tinodes sanctipauli sp. n., Ecnomus cabayugani sp. n., E. tagbanwae sp. n., Hyalopsyche palawanensis sp. n., Pseudoneureclipsis extensata sp. n., Helicopsyche forcipula sp. n., Anisocentropus palawanensis sp. n., Leptocerus palaservius sp. n., Leptocerus membranellus sp. n., Tagalopsyche brunneoides sp. n. and Oecetis ausani sp. n. All male genitalia are illustrated, supplemented by the female genitalia for some species. The illustrations of the male genitalia of an unnamed species of Triplectides Kolenati, 1859 (Leptoceridae) are provided. The relationship of the new species to congeners is briefly discussed. The subfamilies Hyalopsychinae (Dipseudopsidae), represented by two species, and Pseudoneureclipsinae (Dipseudopsidae), represented by one species, are recorded from Palawan for the first time. The genus Pahamunyana Schmid, 1958 (Poycentropodidae) is a new country record.